Classical ion–grain scattering in plasmas: Image force correction. Issue 2 (19th December 2017) - Bastykova, N.Kh.; Kodanova, S.K.; Ramazanov, T.S.; Moldabekov, Zh.A.
Abstract : Corrections to the classical ion–grain scattering and capture cross‐sections due to polarization charges on the dust particle, which acts as an image charge, have been obtained for a low‐charged grain (with the charge number Z  = 10). The trajectory of the ion around the dust particle is used for visual illustration of the influence of the grain polarization on scattering. The correction to the scattering cross‐section due to the image force can be as large as 25% in the strong ion–grain coupling regime and up to 10% in the moderately coupled case. The correction to the capture cross‐section turns out to be nearly constant (∼14%) for moderate as well as strong ion–grain coupling.